Syllabi for statics courses - Rambo-Hernandez, Karen, author; Fontane, Darrell, author; Balgopal, Meena, author; Atadero, Rebecca, author (Colorado State University. Libraries, 2014)
The two syllabi included in this document were used during statics courses that were taught as part of a research study on the effect on student outcomes of introducing projects to a traditional lecture course.

While projects appear to have much to offer engineering education, rigorous evaluations of the impact of projects on student outcomes are rare. The objective of the project is to study the incorporation of three group design projects into a sophomore level statics course and to measure the effect of the changes on student outcomes including content knowledge and various affective outcomes.
Research Initiation Grant: Problem/Project-Based Learning in Statics, a Stepping Stone to Engineering Education Research.
Keywords: curriculum; communication; teamwork; engineering education; student design projects; evaluation tools; evaluation findings